New dinuclear cyanido complexes with amine alcohol ligand: synthesis, characterization and biotechnological application potential - N. Korkmaz; Ş. A. Korkmaz; Y. Ceylan; R. İmamoğlu; A. S. Bülbül; A. Karadağ (The Ukrainian Biochemical Journal, 2022)
In this study, the cyanido complexes given by the formula [Ni(Abut)Ni(CN)4]·8H2O (C1), [Cu(Abut)2Ni(CN)4]·7H2O (C2), [Zn(Abut)Ni(CN)4]·8H2O (C3) and [Cd(Abut)Ni(CN)4]·7H2O (C4) were obtained by microwave synthesis method. The powder forms of the complexes were characterized by elemental, FT-IR spectroscopy, and thermal analysis. And also antibacterial, antibiofilm and anticancer activities were investigated. The splitting stretching bands of cyanido groups in the FT-IR spectra of C1-C4 indicated the assets of terminal and end cyanido groups. The antibacterial activities of C1-C4 were tested with nine Gram negative and six Gram positive bacteria. The most efficient antibacterial activity of complexes was observed at 1000 µg/ml-1 concentration. Anticancer activity was tested using HeLa cell line and MTT test. The studied cyanide complexes have been shown to decrease the viability of HeLa cells with IC50 values 14.86, 6.5, 7.2 and 19.2 µg/ml for C1, C2, C3 and C4 complex, respectively.